Blockchain-Based Data Storage for Internet of Things Networks - Jerbi, Wassim; Cheikhrouhou, Omar; Guermazi, Abderrahmen; Trabelsi, Hafedh (International journal of business data communications and networking, 2024)
Consensus mechanisms are fundamental to blockchain technology, ensuring network integrity and the orderly progression of transactions. However, the predominant proof of work method, while widely adopted, has raised concerns regarding its energy-intensive nature and lack of scalability. In response, this research explores alternative consensus methods tailored to participants' engagement in blockchain storage activities. We conducted a comprehensive review of existing approaches, examining their reusability and efficacy. Concurrently, we observed a growing demand for distributed storage solutions driven by escalating data volumes. Our investigation identified areas for improvement in existing storage blockchains, motivating the development of our own system, BlockStock. This protocol, meticulously designed, aims to enhance intelligent data storage management reliably and robustly. Through rigorous performance evaluations, including assessments of power consumption, throughput, and data transfer times, BlockStock demonstrates superior efficacy and cost-effectiveness. These findings underscore its significance as a notable advancement in blockchain-based storage solutions, offering a promising avenue for future research and application.